Maternal perception and fear on the adverse effects of immunization, Surabaya City - Maulana, Mulyanti Ayu Wulandari; Sintari, Made Nita; Hargono, Arief (Intelektual Pustaka Media Utama, 2023)
The achievement of immunization has become a global focus, not only in Indonesia. Maternal perception is one of the factors in increasing complete basic immunization (IDL) status in an area. The aimed to analyze several perceptions and fear of the adverse effects of mothers with IDL status in non-universal child immunization (UCI) urban village areas in Surabaya City. A cross-sectional study was conducted from September 2019 to May 2020. The sample was the community taken from the baseline data survey on IDL problems in non-UCI villages in Surabaya City in 2017. The five variables are the mother's characteristics, the mother's fear of the adverse effects of immunization, the belief/culture, the mother's busyness, and the family support that can be changed in maternal perception. The Chi-square test and a logistic regression test were both used in the multivariate analysis. And 1,449 mothers were included. The mother's perception that has the most influence is the mother's fear of the adverse effects of immunization with an OR of 10.139 at 95% CI (4.063–25.302). The findings show that they need to get an education or socialization from health professionals, collaborate with religious community leaders, as well as getting health campaigns.